(untitled) (Applied Biological Research, 2012)
This study was designed to determine pesticide residues in blood, evaluate its effect on biochemical parameters and assess adverse health effects in farmers, pesticide market-workers and pesticide spray workers. The level of awareness or knowledge about precautionary measures for pesticides safety was also assessed. The field survey indicated that 40.0, 6.7 and 12.0% of farmers, market-workers and spray-workers, respectively, did not wear protective clothing. However, most of them (83.3, 93.3 and 88.0%) had knowledge about the safety precautions to be taken during pesticide formulation and application. Significant decrease in hemoglobin level and platelet count was detected in spray-workers, but significant increase in white blood cell count was noticed in pesticide-market workers and spray-workers. No significant changes were observed in liver function, but significant inhibition in acetylcholine esterase activity and significant increase in prothrombin time were noticed in all pesticide-exposed subjects. A significant rise in urea concentration was observed in pesticide-spray workers, but no significant differences in creatinine level were seen. The residue analysis revealed that 76.7, 92.5 and 100.0% of farmers and market- and spray workers, respectively, had insecticide residues in their blood. Also, most of the study subjects had multiple residues above the acceptable daily intake. Therefore, creating the awareness among pesticide users to improve and encourage safe use and handling of pesticides through education, proper guidance and fore-warning about the risks involved in misuse of poisonous materials are required.